Comparative study on performance of manufactured steel fiber and shredded tire recycled steel fiber reinforced self-consolidating concrete. (10th January 2021) - Simalti, Ashish; Singh, A.P
Abstract: The major issues related to the environment are the depletion of natural resources and the dumping of waste materials to the open landfill. Waste tire contributes to the latter problem enormously because it requires large space to dump and which may prone to fire hazards (produced harmful gases like carcinogens) when stockpiled. Recycling of waste tire contributes to solving above mentioned issues by using the recovered material like steel fiber and crumbed rubber etc. in the construction industry. This experimental study presents the fresh and harden (i.e. mechanical and durability) behavior of recycled steel fiber (RSF) extracted from the shredded tire in self-consolidating concrete (SCC). To characterize the above properties, a total of seven mixes were prepared, one control mix i.e. SCC with no fiber, SCC with manufactured steel fiber (MSF), and RSF, each of volume fractions of 0.5%, 1.0%, and 1.5% respectively. Fresh properties were characterized by slump flow and J-Ring test, for checking to fill and passing ability respectively. Whereas, the mechanical properties were investigated in terms of compressive, split tensile, and flexural strength. Further, rapid chloride penetration test (RCPT) and ultrasonic pulse velocity tests were conducted for durability and nondestructive test respectively. Optimization results show that SCC with RSF exhibits overall best performance with a 1.5% volume fraction of RSF as compared to SCC with MSF. With R 2  ≥ 0.7, a good correlation was found between fresh, Mechanical, and durability properties. Further, based on global warming potential it is beneficial to use SCC with RSF over SCC with MSF having lesser carbon emission. So, the SCC with RSF is a sustainable and economically viable solution over the SCC with MSF.